1994
DOI: 10.1172/jci117535
|View full text |Cite
|
Sign up to set email alerts
|

A mannose receptor mediates mannosyl-rich glycoprotein-induced mitogenesis in bovine airway smooth muscle cells.

Abstract: IntroductionThe putative mannose receptor (MR), previously implicated in mannosyl-rich glycoprotein-induced mitogenesis in bovine airway smooth muscle (ASM) cells, was studied to determine its properties. (7). The mitogenic effect is blocked by yeast mannan, a mannose receptor (MR) blocker (8), but not by mannose-6-phosphate, a specific blocker of the cation independent mannose-6-phosphate/insulin-like growth factor II receptor (9), suggesting the involvement of a mannose-recognizing moiety (7).The well-studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 49 publications
(32 reference statements)
3
33
0
Order By: Relevance
“…Several lectin receptors, including the mannose receptor family, are involved in the capture of glycosylated antigen [2] and possibly more than one lectin receptor may be expressed by cattle DC, as has been reported for human macrophages [60]. Lectin receptors are known to effectively mediate uptake by endocytic routes involving small coated vesicles [52,61]. In this respect, the slightly reduced Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Several lectin receptors, including the mannose receptor family, are involved in the capture of glycosylated antigen [2] and possibly more than one lectin receptor may be expressed by cattle DC, as has been reported for human macrophages [60]. Lectin receptors are known to effectively mediate uptake by endocytic routes involving small coated vesicles [52,61]. In this respect, the slightly reduced Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Although both are expressed on macrophages (18,35), Endo180 is also found on fibroblasts and chondrocytes, chondrocytes, a subset of endothelial cells, and in tissues undergoing ossification (1, 17, 18, 38 -40), whereas the mannose receptor has been detected on lymphatic and hepatic endothelium, smooth muscle cells, and some epithelia (41)(42)(43)(44). These differences in distribution may reflect accessibility to distinct sets of ligands in vivo.…”
Section: Figmentioning
confidence: 99%
“…Therefore, we suggest that this enzyme could participate in airway inflammation and remodeling. β-hex and other mannosyl-rich lysosomal hydrolases are potent mitogens for bovine airway smooth muscle cells [24], and this mitogenic action is mediated via airway smooth muscle mannose-recognizing receptors [25] that have been isolated from bovine airway smooth muscle cells and human bronchial smooth muscle [26]. Lew et al [27] demonstrated that β-hex-induced airway smooth muscle cell proliferation is mediated by activation of p21Ras/MEK/p44/42 MAPK and protein kinase C. β-hex causes activation of p44/42 MAPK that is late in onset (30 min) and sustained for 4 h [27].…”
Section: Discussionmentioning
confidence: 99%